On the Dialogue of Aesthetics and Philosophical Anthropology - Apostolopoulou, Georgia (Տիգրան Մեծ)
After the alleged ‘ends’ of metaphysics, of history, and of art, aesthetics reorganises the field of its enquiry. While retaining the question of the meaning of art for the human as the background jus-tification of its theorising, aesthetics meets philosophical anthropology and enlarges its field. Philo-sophical anthropology explains that the instability of the human condition demands culture as the artificial stabilisation of the human world as well as of the human in the world. Expressivity, artifi-ciality, and the aesthetic are interweaved with the meaning of the human world. In this context, pic-tures have priority over concepts and justify art as the eminent pictorial form of meaning. Since the human lives in nature and culture, the stabilisation of its open world is possible through creation of spatial correlates and of objects as well. Thus, aesthetics does need to expand enquiry beyond the discourse on art, so that it includes the issues concerning the aesthetic character of the human world and its spatial correlates. While Wolfgang Welsch and Richard Shusterman argue for a revision of aesthetics, Joseph Margolis and Helmuth Plessner support the stronger dialogue between philosoph-ical anthropology and aesthetics in different ways. Further, Arnold Berleant explores aesthetics of human space. Keywords: aesthetics, philosophical anthropology, aesthetics of spatiality, Wolfgang Welsch, Richard Shusterman, Helmuth Plessner, Joseph Margolis, Arnold Berleant. After the alleged ‘ends’ of metaphysics, of history, and of art, aesthetics reorganises the field of its enquiry. It moderates their radical expression through interpretations that renew theorising on the question of art towards new forms of aesthetic creativity. Without historicist or normative demands, when considering art and the field of the aesthetic, aesthetics retains the question of the meaning of art for the human as the background justification of its status as a philosophical discipline. With reference to this question, aesthetics meets philosophical anthro-pology and can receive from the latter impulses sustaining its enlarged theorising. Recent theories of aesthetics, while weak-ening the discourse of the end of art, perform a moderate shift towards issues and problems, which one could consider as anthropological ones.
Keywords: Philosophy